2021
DOI: 10.1021/acs.jpcc.1c07024
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Catalytic Activity of the Preferred Nitrogen Configuration on the Carbon Nanotube Surface and Its Implications for Li–O2 Batteries

Abstract: Unraveling the catalytic potential of nitrogen-doped carbon nanotubes (NCNTs) for the electrochemical reaction in a Li−O 2 battery (LOB) is of great significance for the preparation of highly active catalysts to overcome the sluggish kinetics. Herein, the surface properties, reaction mechanism, and product behavior on NCNT cathodes are investigated for LOBs using periodic density functional theory. Our calculations demonstrate that the electron-withdrawing nature of N atoms shortens the surrounding N−C and C−C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…However, the ratio of Li 2 CO 3 on the fully charged electrodes shows a significant decreasing trend for pristine and TAPP- and Co-TAP-containing batteries (80.2%, 44.3%, and 17.6%, respectively, Figure S5a–c), indicating that parasitic reactions are suppressed by adding TAPP or Co-TAP RMs, especially Co-TAP. Generally, Li 2 O is reported to be not easily decomposed during charging in LOBs . However, for both pristine and TAPP-containing batteries in this study, Li 2 O disappears entirely after charging.…”
mentioning
confidence: 54%
See 1 more Smart Citation
“…However, the ratio of Li 2 CO 3 on the fully charged electrodes shows a significant decreasing trend for pristine and TAPP- and Co-TAP-containing batteries (80.2%, 44.3%, and 17.6%, respectively, Figure S5a–c), indicating that parasitic reactions are suppressed by adding TAPP or Co-TAP RMs, especially Co-TAP. Generally, Li 2 O is reported to be not easily decomposed during charging in LOBs . However, for both pristine and TAPP-containing batteries in this study, Li 2 O disappears entirely after charging.…”
mentioning
confidence: 54%
“…Generally, Li 2 O is reported to be not easily decomposed during charging in LOBs. 38 However, for both pristine and TAPP-containing batteries in this study, Li 2 O disappears entirely after charging. These results were also confirmed by Li 1s XPS spectra (Figure S6a−c).…”
mentioning
confidence: 56%
“…With this in mind, various physical and chemical modifications, such as heteroatom doping, have been applied to improve the catalytic activity of carbon materials. The charge redistribution caused by the difference in electronegativity between heteroatoms and carbon atoms can impart carbon with a whole new electrochemical property [84] . Yi et al found through calculations using periodic density functional theory that doping N atoms on the surface of CNTs affects both the atomic distribution and electrical conductivity.…”
Section: Oxygen Cathodementioning
confidence: 99%
“…In addition to carbon compounds doped with heteroatoms such as N and P, there are rarely reported carbon materials doped with F [84] . Due to the high electronegativity of F, the semi-ionic C-F bond produced by F renders the carbon doped with F acidic and appears as an electron acceptor, leading to an extremely stable material with enhanced electron transfer capability [86,87] .…”
Section: Oxygen Cathodementioning
confidence: 99%
“…Considering that the specific behavior of lithium oxides in LOBs is difficult to be tracked and captured, the inadequacies of the experiment are inevitably highlighted. In recent years, micro-theoretical calculations, mainly including density functional theory (DFT) and molecular dynamics (MD), have become one of the indispensable research methods in revealing reactions, interfaces, and interactions. , Computations not only provide important insights into the electrochemical mechanism but also shed more light on the design and improvement of experimental programs and material preparation.…”
Section: Introductionmentioning
confidence: 99%